2018
DOI: 10.3332/ecancer.2018.830
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality management of leiomyosarcoma of the cervix

Abstract: We present the case of a young female patient who presented to the outpatient department with a history of bleeding per vagina, diagnosed with leiomyosarcoma of the cervix; the patient underwent total abdominal hysterectomy with pelvic lymph node dissection. In this article, we mainly discuss multimodality therapy in the management of an unusual variety of tumour in the uterine cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Hysterectomy should be the first choice of treatment in these patients according to other studies. Multimodality management may suitable for cervical leiomyosarcoma [ 11 ]. Undifferentiated sarcomas are a rare group of tumors with an aggressive behavior and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hysterectomy should be the first choice of treatment in these patients according to other studies. Multimodality management may suitable for cervical leiomyosarcoma [ 11 ]. Undifferentiated sarcomas are a rare group of tumors with an aggressive behavior and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Spindle cell tumours may be sarcomas or carcinomas, and can also be benign [ 6 ], as in the index case. Few cases of spindle cell neoplasm of the cervix are reported in the literature [ [7] , [8] , [9] , [10] , [11] ], limiting the knowledge about its characteristics, and making this case report relevant. The occurrence of only spindle cells in the tumour without the presence of other cells makes this case rare.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy is often used to decrease locoregional recurrence. The regimen consists of the administration of external radiotherapy of 50 Gy in 25 fractions followed by 2-3 sessions of brachytherapy 15 . In a retrospective review of 208 patients, it was observed that treatment with adjuvant pelvic radiotherapy decreased the risk of pelvic recurrence 16 .…”
Section: Discussionmentioning
confidence: 99%